(3CSGSjGJ GdLZQGajI GdHTQjIs - (3YHGS aGVd(B, (3GdSYOjs ((3YeGf(B:s (3eDSSI GdhQGb(B,s, 2002)
(3GdLZQGajI GdHTQjI heOGQSgG,GdEfSGf,GdEfSGf hGdHjFI GdWHjYjI,GdGbJUGO GdHTQj,GdGSJjWGf GdHTQjs
(3eUGOQ HGddZI GdYQHjI U(B.453(3; eUGOQ HGdZI GdEfcdjRjI U(B.467 (3jhLO faS GdcJGH HQbe C(B/1788s
Keywords: (3GdLZQGajG GdHTQjIs